Development of a discharge education program using the teach-back method for heart failure patients - Eui Geum Oh; Hyun Joo Lee; You Lee Yang; Sewon Lee; Young Man Kim (BMC, 2021)
Abstract Background Heart failure (HF) patients have difficulties in self-management after discharge. This study aimed to develop a discharge education program for HF patients using the teach-back method (TBM). Methods As a methodological study to develop a program, we applied the analysis, design, development, implementation, and evaluation (ADDIE) model comprised of (1) analysis using EMR data, systematic review, and focus group interviews, (2) design and development of a program draft, (3) tests of program validity using 15 experts, 10 nurses, and 10 patients, and (4) development of the final program. The content validity index (CVI), and understandability and actionability of the educational material were used. Results The discharge education program provides definitions and information about medication, symptom/weight/diet management, physical activity, and other precautions. The educational method uses TBM. The overall CVI for the program was 0.96, and all item CVIs were greater than 0.8. The understandability and actionability were 90.2 and 91.3 % in patients, and 94.6 and 86.8 % in nurses. The contents and methods of the program were appropriate for patients and providers. Conclusions We expect the discharge education program using TBM to enhance self-management among HF patients. The process we used to develop this program could guide researchers and clinical practice.